2014
DOI: 10.1177/1356336x14555293
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity levels and motivational responses of boys and girls

Abstract: The purpose of this study was to independently determine the levels of moderate-to-vigorous physical activity (MVPA) and self-determined motivation of both boys and girls as they participated in prolonged units of invasion games (i.e. 6–12 lessons) through two pedagogical models: direct instruction and the tactical games model (TGM). It was hypothesized that given the differences in domain interaction and lesson structure, both boys and girls would gain higher levels of physical activity (PA) and possess highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 41 publications
2
25
0
1
Order By: Relevance
“…Gray et al (2009) showed that the implementation of the TIG, in contrast to the traditional approaches, increases the opportunities to play the game, and consequently, improves the students' decision-making intelligence. Similarly, Smith et al (2014) observed an increase in the amount of moderate-tovigorous physical activity among TGM students in contrast to DI students. However, when these results are divided by gender, discrepancies are observed: female TGM students do not meet the 50% of physical activity level recommended for PE sessions (Hartwig et al, 2019).…”
Section: Implementation Of Games-centered Approach and Its Impact On mentioning
confidence: 74%
See 1 more Smart Citation
“…Gray et al (2009) showed that the implementation of the TIG, in contrast to the traditional approaches, increases the opportunities to play the game, and consequently, improves the students' decision-making intelligence. Similarly, Smith et al (2014) observed an increase in the amount of moderate-tovigorous physical activity among TGM students in contrast to DI students. However, when these results are divided by gender, discrepancies are observed: female TGM students do not meet the 50% of physical activity level recommended for PE sessions (Hartwig et al, 2019).…”
Section: Implementation Of Games-centered Approach and Its Impact On mentioning
confidence: 74%
“…Videorecording sessions and BEST (Sharpe and Koperwas, 1999) Teaching behavior related to motivational climate TEGQ (Papaioannou et al, 2007) Motivational climate students' perception Smith et al (2014) PE−2 groups. Trad.…”
Section: (Basketball)mentioning
confidence: 99%
“…On the other hand, in the DI method, the students participate in technical components or drills. The teacher gives direct information to the students including prescriptive feedback, and they execute according to the guidelines given [9,10]. The TGA method is more successful than the DI method because it bases its learning on small-sided games.…”
Section: Introductionmentioning
confidence: 99%
“…In the study made by Chatzipanteli et al (2016), as a result of the first test and final test assessments on the increase in the metacognitive behavior of students for the Tactical Game Approach in the volleyball branch of learning, they stated that the metacognitive behavior increased at the level of 22.53% with the Tactical Game Approach model. In the study made by Smith et al (2015) to compare the Direct Learning Model and the Tactical Game Model for determining the physical activity levels and motivational reactions of females and males in physical education courses (6-12 weeks), they stated that from the aspect of motivation there was an insignificant difference for males and females in both groups and from the aspect of the level of physical activity, there was a significant difference between the first test -final test in females in the Tactical Game Group.…”
Section: Discussionmentioning
confidence: 99%
“…The process of implementation of a teaching technique in a class environment can be composed in very different structures according to different subject fields and different class levels (Aelterman et al, 2013). In general, the direct teaching model implemented in physical education courses is structured in the manner of showing examples with the control of the teacher, step-by-step advancement, using visual elements and presenting feedback (Smith et al, 2015). While a limited opportunity is given within the class for students to make decisions, most of the time, the responsibility is given only to follow the instructions of the teacher (Roberts & Fairclough, 2011).…”
Section: Introductionmentioning
confidence: 99%